Cotranslational protein folding - fact or fiction? - Deane, C; Dong, M; Huard, F; Lance, B; Wood, G (Oxford University Press, 2007)
Motivation: Experimentalists have amassed extensive evidence over the past four decades that proteins appear to fold during production by the ribosome. Protein structure prediction methods, however, do not incorporate this property of folding. A thorough study to find the fingerprint of such sequential folding is the first step towards using it in folding algorithms, so assisting structure prediction. Results: We explore computationally the existence of evidence for cotranslational folding, based on large sets of experimentally determined structures in the PDB. Our perspective is that cotranslational folding is the norm, but that the effect is masked in most classes. We show that it is most evident in α/β proteins, confirming recent findings. We also find mild evidence that older proteins may fold cotranslationally. A tool is provided for determining, within a protein, where cotranslation is most evident.